LOLODA IN THREE TERNATE-DUTCH TREATY MANUSCRIPTS IN 19th CENTURY - Christomy, Tommy; Suharjo, Rias (International Review of Humanities Studies, 2019)
The impact of the relationship between Ternate and Europe affected the relation between Ternate and its surrounding area. As a result of the socio-political dynamics with the colonial, Ternate did not easily positioned itself as a sultanate which was neutral from the Dutch and the interest of its surrounding kingdoms, especially its neighbouring sultanate. Ternate was dragged into alliance with Dutch in order to secure access toward the natural resources needed by both parties. One of the tools used by Dutch in 19th century to secure access toward natural resources was the treaty. The treaty between Ternate and Dutch became an important instrument to maintain legitimacy of the two parties. Loloda was amidst the interest of Ternate and Dutch. In some treaties, the signature of Loloda Sultanate and other small sultanates in North Maluku which were Ternate loyalists were needed by Dutch and Ternate. Therefore, we could easily draw a conclusion based on the treaty that Loloda is part of Ternate’s hegemony. However, in this research we will explore poetically the relation between the Dutch, Ternate and Loloda expressed through metaphor and other specific expressions. For this reason, we will discuss in depth the poetic aspects of three manuscripts (113/1/14, 113/8/11a, dan 113/8/12).